Students’ Perceptions of Using Poised Website for Practicing Public Speaking - Siti Sholikhah; Ahmad Amin Dalimunte (South Sulawesi Education Development (SSED), 2025)
Public speaking is an essential skill for students, yet many face anxiety and lack confidence when speaking in English. This study investigated students' perceptions of using the Poised website, an AI-based public speaking practice tool, to enhance their speaking abilities. The research involved ten senior high school students who practiced using Poised for seven days. Data were collected through observations, recorded speech sessions, and semi-structured interviews. The findings revealed that Poised helped to improve students’ self-confidence, vocabulary acquisition, pronunciation, fluency, and ability to maintain conversation flow. Additionally, students appreciated the structured feedback provided by the platform, which helped them identify areas for improvement. However, challenges such as internet dependency, limited language options, and monotonous AI-generated feedback were also identified. This study contributes to understanding how AI-powered platforms can support English language learning and highlights areas for improvement in technology-assisted speaking training. Further research is recommended to explore long-term effects and potential integrations of AI tools with interactive learning methods.